2014
DOI: 10.1167/iovs.13-12626
|View full text |Cite
|
Sign up to set email alerts
|

A New Adjustable Glaucoma Drainage Device

Abstract: The resistance to outflow of the experimental AGDD can be adjusted to keep IOP in the desired physiological range. This feature could be useful for addressing the risk of hypotony in the early postoperative stages and could provide a means to achieve optimal IOP under a wide range of postoperative conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…25 There are several novel devices with adjustable valve mechanisms in published reports. [26][27][28] In principle, having control of the pressure postoperatively seems ideal. Unfortunately, these devices incorporate complex mechanisms for outflow resistance compared to a valveless system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 There are several novel devices with adjustable valve mechanisms in published reports. [26][27][28] In principle, having control of the pressure postoperatively seems ideal. Unfortunately, these devices incorporate complex mechanisms for outflow resistance compared to a valveless system.…”
Section: Discussionmentioning
confidence: 99%
“…30 In these devices, very small changes in inner diameter over such a short length can have very significant changes in outflow resistance. In addition, several of these devices 26,27 use magnetic components, and we suspect that patients with these devices would not be able to undergo magnetic resonance imaging (MRI). Adjustable devices will also ultimately be limited by fibrosis, so the utility of the adjustable valve would be short-lived.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of the AGDD system was first described by Stergiopulos,11 further developed and patented by Bigler 12 and Stergiopulos, 11 and described in details by Villamarin et al 10 Briefly, the system comprises the AGDD implant and the external measurement/adjustment device, hereafter called the control unit (CU; Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a new experimental noninvasively adjustable glaucoma drainage device (AGDD) has been developed. 10 In vitro results demonstrated that the fluidic resistance of the device can be adjusted to consequently regulate the IOP. To assess the safety and the efficiency of the novel device, we report the first in vivo testing of this AGDD.…”
mentioning
confidence: 99%
“…In fact, the residual resistance provided by the tube might be detrimental in achieving lowest possible IOP once the bleb resistance have formed surrounding the plate. This issue of residual resistance can potentially be tackled by the eyeWatch implant, 24 the eyeWatch implant utilises a magnetic compression mechanism onto the external portion of the tube. The amount of squeeze on the tube can be adjusted postoperatively in the clinic using a magnetic device.…”
Section: New Generations Of Glaucoma Tube Implantmentioning
confidence: 99%